Pengaruh Penambahan Dekstrin dan Albumen Telur (Putih Telur) Terhadap Mutu Tepung Pisang Matang - Riyanti Ekafitri; Diki Danang Surahman; Nok Afifah (Institution for Industrial Research and Standardization of Industry - Padang, 2016)
Ripe banana flour has disadvantage such as poor physical properties. This research aims to determine whether adding the dextrin and albumen (egg white) can improve the physical properties, nutritional values, and acceptance of ripe banana flour. The research design used completely randomized design with 3 treatments namely ripe banana flour control, with the addition of dextrin and the addition of albumen (egg white) foam. Analysis of the product was chemical analysis (moisture, fat, protein, ash and carbohydrate, pH, and TSS), physical properties (yield, whiteness, water holding capacity), and sensory analysis. The results showed that the addition of albumen (egg white) foam increased protein (10.40%) and ash content (2.97%), as well as increased the pH value (4.97), and the WHC at temperature 40oC (0.85) and at temperature of 80°C (1.81). The addition of dextrin increased the carbohydrate content (87.07%) and TSS (6.37o brix). Ripe banana flour without addition dextrin and albumen (egg white) produced banana flour with the highest water and fat content of 9.08% and 0.34%, and the highest yield, whiteness, and highest score of sensory acceptance: 18.42%; 26,24%; and 4,93. The addition of dextrin and egg white foam increased nutritional values such as protein, ash, and fat content of ripe banana flour, and also the pH value, TPT, and WHC, but did not improve yield and whiteness as well as sensory acceptance of ripe banana flour.ABSTRAKPengembangan mesin pengurai serat tandan kosong kelapa sawit dilakukan untuk menghasilkan serat mekanis sebagai penguat papan partikel. Didalam penelitian ini dilakukan perancangan mesin, pembuatan mesin dan evaluasi teknis kinerja mesin. Evaluasi teknis dilakukan pada putaran 600 rpm dan 900 rpm dengan masing-masing putaran 2 kali penguraian, dan masing-masing penguraian 3 ulangan. Dari hasil rancangan mesin didapatkan kapasitas mesin ± 200 kg/jam dan daya penggerak 5 HP. Hasil evaluasi teknis kinerja mesin didapatkan persentase serat dan serat campuran pada putaran 900 rpm pada pengujian 1 dan 2 tidak berbeda jauh dengan pengujian pada putaran 600 rpm. Dari 10 kg TKKS cacahan masing-masing putaran, didapatkan rata-rata serat bersih 82%, serat campuran 14%, dan 4% menjadi debu. Dari hasil penguraian pada putaran 600 rpm dan 900 rpm didapatkan 5 macam komposisi tingkatan serat yaitu, a) serat bersih 600 rpm, b) serat bersih 900 rpm, c) serat campuran (2-3 cm+kelopak), d) serat campuran (<2 cm + kelopak), e) serat campuran (serat halus + serbuk). Hasil analisis kimia ke lima serat tersebut yaitu, rata-rata kadar air serat 9,3%, kadar ekstraktif 5,6%, kadar lemak 1,4%, kadar lignin 33,1%, kadar holoselulosa 58,33%, dan selulosa 39,2%. Dibandingkan dengan serat kayu daun jarum dan kayu meranti merah, kandungan kimia serat tersebut hampir sama atau tidak berbeda jauh.